О межкультурной осведомленности студентов-русистов (на материале эмпирических данных) - Anna Żebrowska (Studia Rossica Posnaniensia)
In the age of a rapid development of technology and communication intercultural education plays a special role. The goal of this education is to develop and shape intercultural competence. A purposeful and carefully considered process is needed to achieve this. The process consists of several stages, of which the most important is teaching/learning a foreign language based on the student’s native language and culture. This means that, apart from knowing certain elements of another culture, a student should have a thorough knowledge of his/her own country, history and culture. However, it often turns out that students know more about the culture of a given foreign country and nation than about their own culture. The study presented in this article confirms this hypothesis, and thus clearly emphasizes the need for improving the content of the syllabus as well as the methods of teaching foreign languages in Polish educational centers.